Partial crystallization in Pd-BMG systems: From understanding structure towards influencing functionality through temperature-time series - SabrinaL.J. Thomä; Robert Zboray; Anthony Chevalier; Ruggero Frison; Romuald Sauget; Silke Prades-Rödel; Roland Logé; Andreas Blatter; Alex Dommann; Antonia Neels (Journal of Materials Research and Technology)
Small quantities of crystalline domains created in an amorphous matrix are seen as an active driver for enhanced properties in bulk metallic glasses (BMGs). We investigated partial crystallization and phase transformations through a series of isotherms at 370°C performed on amorphous Pd-based BMG samples with the nominal composition of Pd43Cu27Ni10P20 (Pd-BMG) and a density of 9.425 g/cm3. X-ray based methods such as X-ray diffraction (XRD) and phase enhanced micro-computed tomography (μ-CT) have been pushed to their limits for studying atomic structure and morphology, while time available before crystallization has additionally been investigated via differential scanning calorimetry (DSC), and are combined with optical microscopy (OM), scanning electron microscopy (SEM), and hardness measurements for their mechanical properties. We reveal that Pd-based BMG samples isothermally treated at 370 °C start to crystallize after 20 min and still undergo phase transformations and recrystallization even after being fully crystalline after 60 min of the isothermal treatment. Interestingly, 3D phase enhanced micro-computed tomography shows a clear separation of two domains of slightly different densities. We highlight X-ray tomographic scans, allowing the 3D spatial visualization of extremely low-density contrast in different material domains, thus providing a multi-scale physical description of the Pd-BMG system. Interesting is the fact, that the re-crystallization is not homogenous and the crystalline domains can reach large size of (100–200 μm) in an amorphous matrix.